2018
DOI: 10.1002/jum.14795
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Intraventricular Pressure Using Ultrasound Elastography

Abstract: We have shown that SWEI measurements are linearly related to IVP; therefore, pressure-based indices could potentially be derived from SWEI ultrasound elastography. The feasibility of using SWEI to estimate IVP with a single point calibration was also shown in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Therefore, a high correlation between SWV values and cardiac function parameters such as contraction efficiency and relaxation rate were determined, as well as a moderate correlation between SWV values and graft workload and end-diastolic pressure [ 25 ]. SWV has also been utilized to perform similar measurements on rabbit hearts during Langendorff machine perfusion and working heart modality, where the SWV values correlated to myocardial contractility, diastolic function, and intraventricular pressure [ 26 30 ]. The value of SWV as an assessment technique, if further developed, could be immense due to its capabilities for providing quantitative measurements of a given graft’s relative transplantability preserved via SCS or machine perfusion.…”
Section: Novel Imaging-based Experimental Assessment Techniquesmentioning
confidence: 99%
“…Therefore, a high correlation between SWV values and cardiac function parameters such as contraction efficiency and relaxation rate were determined, as well as a moderate correlation between SWV values and graft workload and end-diastolic pressure [ 25 ]. SWV has also been utilized to perform similar measurements on rabbit hearts during Langendorff machine perfusion and working heart modality, where the SWV values correlated to myocardial contractility, diastolic function, and intraventricular pressure [ 26 30 ]. The value of SWV as an assessment technique, if further developed, could be immense due to its capabilities for providing quantitative measurements of a given graft’s relative transplantability preserved via SCS or machine perfusion.…”
Section: Novel Imaging-based Experimental Assessment Techniquesmentioning
confidence: 99%
“…Thus, an expression for β in terms of stress can be produced by substituting (19) into (18), which results in…”
Section: B Spherical Pressure-vessel Model Of the Bladdermentioning
confidence: 99%
“…These measurements can also sort out the remaining uncertainties in literature how other factors such as loading but also a combination of contractility and intrinsic stiffness (in for example an infarct) affect SWE measurements in diastole and systole. A preload independence of diastolic and systolic wave speed measurements has been suggested 2 , whereas other studies showed that an increase in ventricular or intra-myocardial pressure affected wave propagation speed in a Langendorff-prepared set-up 8 , 9 . We therefore hypothesized that increased ventricular pressure can induce an apparent stiffening of the myocardium due to the intrinsic material non-linearity.…”
Section: Introductionmentioning
confidence: 99%